Pengaruh Pemberian Terapi Obat Anti Tuberkulosis Fase Intensif terhadap Kualitas hidup Penderita Tuberkulosis di Kota Kupang - Tanof, Verentika Putri; Buntoro, Ika Febianti; Trisno, Idawati (Universitas Nusa Cendana, 2022)
Background : Tuberculosis (TB) is a direct infectious disease that can attack various organs or tissues of the body caused by the Mycobacterium tuverculosis bacteria. Patients with pulmonary TB often become very weak due prolonged chronic illness, weight loss, chest pain and shortness of breath. Intensive phase of pulmonary TB treatment administered for 2 months with OAT consist of isoniazid, rifampisin, pirazinamid, and ethambutol. OAT not only cures patients and cripples BTA but also has side effects that influence patients. Clinical symptoms and OAT side effects will affect the quality of life of patients with pulmonary TB. Objective : To knowt the influence of anti tuberculosis therapy on the quality of life of pulmonary TB patients. Method : This study used the research design of Quasy-Experimental One Group Pretest and Post Test, to determine the quality of life of patients with pulmonary TB before and after administration of anti-tuberculosis for 2 months conducted in 11 health centers in Kupang by interview using the SF-36 questionnaire. Sampling techniques use consecutive sampling with a total of 44 samples meeting the criteria of inclusion. Research was analyzed Univariate, Bivariate using Test MC Nemar and multivariate using regression logistic multiple test. Results: In this study the test results of MC Nemar showed the value of P = 0,000 (P < 0.05). And the test results regression logistic multiple with the value P = 0.024, which indicate there is a significant influence of intensive phase anti-tuberculosis drug therapy on the quality of life of tuberculosis patients. Conclusion: In this study, it is known that the quality of life of pulmonary TB patients before the administration of intensive phase of anti-tuberculosis drugs is categorized low and after the administration of anti-tuberculosis drugs is categorized high.